2011
DOI: 10.1001/jama.2011.1247
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life, Burnout, Educational Debt, and Medical Knowledge Among Internal Medicine Residents

Abstract: In this national study of internal medicine residents, suboptimal QOL and symptoms of burnout were common. Symptoms of burnout were associated with higher debt and were less frequent among international medical graduates. Low QOL, emotional exhaustion, and educational debt were associated with lower IM-ITE scores.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

28
488
3
17

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 600 publications
(554 citation statements)
references
References 41 publications
28
488
3
17
Order By: Relevance
“…[2][3][4] Similar to previous studies, 2,4 we found no significant associations between resident demographic characteristics and burnout. Our findings of the relationship between job satisfaction (BI enjoy my continuity clinic^) and burnout are also supported by the literature.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…[2][3][4] Similar to previous studies, 2,4 we found no significant associations between resident demographic characteristics and burnout. Our findings of the relationship between job satisfaction (BI enjoy my continuity clinic^) and burnout are also supported by the literature.…”
Section: Discussionsupporting
confidence: 88%
“…1 It is measured using a validated instrument, 1 and reported by 50-75 % of resident physicians. [2][3][4] Burnedout residents self-report increased rates of medical errors, 4,5 suboptimal patient care, 2 and reduced empathy. 6,7 A few studies have tried to substantiate these findings with independent observational data but have not provided confirmatory evidence.…”
mentioning
confidence: 99%
“…Another study of medicine residents noted that senior residents (PGY3) had the highest QOL and more junior residents (PGY1 and 2) and women had more work‐life balance dissatisfaction and emotional exhaustion 16. In that study, the symptoms improved with increased PGY level 16. We speculate this difference in otolaryngology PGY1 versus medicine PGY1 is that medicine residents start within their fields whereas otolaryngology residents begin as rotators.…”
Section: Discussionmentioning
confidence: 78%
“…The burnout effect also appears to have a cumulative effect over time 3. Another study of medicine residents noted that senior residents (PGY3) had the highest QOL and more junior residents (PGY1 and 2) and women had more work‐life balance dissatisfaction and emotional exhaustion 16. In that study, the symptoms improved with increased PGY level 16.…”
Section: Discussionmentioning
confidence: 84%
“…Há uma cultura de que a privação do sono é um símbolo de dedicação à profissão médica, parecendo aumentar a produtividade nos estudos e no atendimento [25]. Entretanto, estudos sugerem que fadiga, sonolência, depressão, esgotamento, insatisfação no trabalho e baixa qualidade de vida podem afetar negativamente o profissionalismo, a qualidade da assistência e a segurança e satisfação do paciente [24,26].…”
Section: Discussionunclassified